In Silico Analysis of Non-synonymous Mutations in the durA Gene and Their Effects on the Stability and Physicochemical Properties of Duramycin - Yulianto Ade Prasetya; Tjie Kok; Mariana Wahjudi (Tropical Genetics, 2025)
Duramycin is a lantibiotic peptide encoded by the durA gene, known for its antimicrobial activity against Gram-positive bacteria. This study aimed to evaluate the effects of single-point mutations on the stability and structural integrity of duramycin using a comprehensive in silico approach. Five variants—C1S, F7A, T11Y, D15E, and K19V—were designed and assessed using I-Mutant2.0 to predict their impact on protein stability. ProtParam analysis was conducted to determine molecular weight, isoelectric point (pI), net charge at pH 7, instability index, aliphatic index, and hydropathicity (GRAVY). In addition, PEP-FOLD3 was employed to model the 3D conformations of each mutant peptide. Results showed that K19V improved peptide stability and increased aliphatic index and GRAVY score, indicating enhanced hydrophobicity and potential thermal stability. In contrast, F7A led to a major structural shift marked by an α-helical conformation and reduced stability. C1S and T11Y induced minor destabilizing effects, while D15E offered a moderately stabilizing substitution with minimal structural deviation. Overall, this study highlights the functional relevance of C-terminal and hydrophobic residues in maintaining duramycin’s structural compactness and provides a framework for future design of optimized antimicrobial peptides through rational mutation